Graves’ disease patients with iron deficiency anemia: serologic evidence of co-existent autoimmune gastritis - Gianoukakis, Andrew G (Am J Blood Res, 2021)
Background: Graves’ disease (GD) has been associated with iron deficiency anemia (IDA). Atrophic gastritis leads to IDA and has been associated with autoimmune thyroid disease. This study prospectively determined the prevalence of atrophic gastritis markers and the relationship between these markers and markers of IDA in GD subjects. Methods: Newly diagnosed GD patients (90) and controls (41) were studied. Of the newly diagnosed GD patients, 65 were consecutively enrolled and identified with GD irrespective of anemia, 25 had GD and IDA. Thyroid function, hematologic indices, and atrophic gastritis markers [parietal-cell antibodies (PCab), Helicobacter pylori antibodies (H. pylori ab), mean serum gastrin levels] were examined. Results: GD patients presenting with IDA were twice as likely (64% vs. 32%, P=0.049) to harbor PCabs when compared to all other GD subjects. Unselected GD subjects (n=65) had significantly higher PCab (37% vs. 7%, P<0.001) compared to controls. Gastrin levels were significantly elevated in all GD subjects compared to controls (105 vs. 39 pg/ml, P<0.0001). This difference was magnified in PCab+ subjects (202 vs. 64 pg/ml, P=0.003). In all GD subjects, PCabs were associated with increased gastrin levels (202 vs. 75 pg/ml, P=0.0004) and lower ferritin levels (52 vs. 95, P=0.05). In GD anemic subjects, PCabs were associated with lower mean corpuscular volume (75 vs. 81, P=0.001). Gastrin levels correlated inversely with ferritin levels in all GD subjects and positively with TIBC in GD anemic subjects. Conclusions: A significant subset of patients presenting with GD may suffer from IDA due to concurrent autoimmune atrophic gastritis.